(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Experiences at time of delivery not only influence women’s self-esteem and mother-child bonding but may also haveimpact on future birthing preferences. Various factors may influence women’s birthing experiences and thus overall maternal healthand utilisation of institutional health services. Respectful maternity care is an individual-centric approach aimed at recognizingwomen’s preferences and needs thereby promoting skilled assistance during childbirth.Objectives: To study various factors affecting women experiences at childbirth at different health care facilities of central India. Togive recommendations for formulating policies towards respectful maternal care.Material and Methods: Descriptive Cross-sectional survey of 510 women delivering at different health facilities conducted over aperiod of 3months at Department of Obstetrics and Gynecology, PCMS, Bhopal. Factors related to pregnant women, family, staff, andhospital setup which may influence women experiences were assessed using a 20-item based questionnaire as tool.Results: Total 510women were interviewed(mean age 27.8yrs, overall literacy rate90%). Overall, 41% reported good birthingexperience. Facility-wise deliveries were, medical college(33%), district hospital and PHC(41%), private set ups(20%), Dai(5%).Factors commonly associated with good birthing experience were delivery at private setup(55%), consideration for privacy(75%),good family support(40%), shorter labour duration(40%), consent prior to examinations(58%), vaginal delivery(43%), adequate painrelief(49%) and good neonatal outcome(44%). Women delivered by Dai(50%), those left unattended(50%) and those experiencingphysical or verbal abuse(75%) reported overall bad experiences. Majority(70%) with good experience looked forward to futurepregnancies.Conclusion: Regular feedbacks and audit of factors influencing women’s birthing experiences take priority. Respectful maternity careby promoting institutional deliveries would thus reduce overall maternal morbidity and mortality.